Lysosomes in biology and pathology. V.2 - Neuberger, A.; Tatum, E. L.; Dingle, J. T.; Fell, Honor B. (Lon Don : North-Holland P.C, 1975)
Contents of this book include: Lysosomes in pathology; Structure and enzymology; The lysosomes in digestion and secretion; Methods for the study of lysosomal function.
Keywords: Lysosomes; Lysosomes -- Biology and pathology